The influence of principal instructional leadership behaviour on the organisational commitment of junior high school teachers in Surakarta - Sukarmin, Sukarmin; Sin, Ishak (Universiti Utara Malaysia Press, 2022)
Purpose – The main objective of this study was to identify the influence of principal instructional leadership on teacher organizational commitment in junior high schools in Surakarta. This issue arises because there are discrepancies in the findings of previous studies as well as the lack of studies in Indonesia. Accordingly, no definitive conclusions can be drawn in relation to this issue which is still pending.